The interactive effect of cultural values and government regulations on firms’ entrepreneurial orientation - Chew Tze Cheng @ Nur Alesha Chew; Tang, Y.K.; Buck, T. (Emerald Group Holdings Ltd., 2021)
Purpose: Considering that the social-cultural context is important as in which the entrepreneurs are embedded to conceptualise entrepreneurial orientation (EO), the purpose of the study is to explicate the influence of the key decision-makers’ internalised cultural values and perceptions of government regulations, to offer nuanced explanations of micro-level variations in EO of firms embedded in the same institutional context. Design/methodology/approach: Using a quantitative approach, relationships are explored in a sample of 201 Malaysian small- and medium-sized enterprises (SMEs). Partial least squares structural equation modelling (PLS-SEM) is used for the sample, and an additional test is conducted for a robustness check. Findings: The study finds that three cultural values of the key decision-maker, namely individualism, masculinity and uncertainty avoidance, exhibit a significant association with the EO of the firms. Further, the analysis reveals that the positive effects of individualism and masculinity are enhanced when moderated by favourable perceptions of government regulations to entrepreneurship. Research limitations/implications: The study uses a single key informant in data collection, therefore, the possibility of single-respondent bias. The results must be interpreted in light of these limitations. Originality/value: The study contributes to the existing literature regarding the relationship between institutions and entrepreneurship. Specifically, it articulates a microfoundations lens to explain the influence of institutions in terms of key decision-makers’ internalised cultural values (informal institutions) and their perceptions of government regulations (formal institutions) on the EO of the firm. It further elucidates the need to embrace informal and formal institutions as interdependent factors instead of treating them as standalone constructs in entrepreneurship research and policy design.